An overall characterization of pediatric acute lymphoblastic leukemia with 2 overexpression. Issue 10 (17th June 2014) - Yano, Mio; Imamura, Toshihiko; Asai, Daisuke; Moriya‐Saito, Akiko; Suenobu, So‐ichi; Hasegawa, Daiichiro; Deguchi, Takao; Hashii, Yoshiko; Kawasaki, Hirohide; Hori, Hiroki; Kosaka, Yoshiyuki; Kato, Koji; et al.
<x xml:space="preserve">Abstract</x> For an overall characterization of pediatric B‐cell precursor acute lymphoblastic leukemia (BCPALL) with CRLF2 overexpression (OE), we conducted genetic analysis of CRLF2 in 167 pediatric BCPALL patients. CRLF2 OE was detected in 30 (18%) of 167 patients, the P2RY8‐CRLF2 fusion was identified in only 3 (1.8%) of 167 patients, all of which demonstrated CRLF2 OE. Moreover, CRLF2 gain was identified in 18 (11%) of 167 patients. Messenger RNA sequencing revealed a novel fusion transcript, CSF2RA‐CRLF2, in a case with CRLF2 OE, suggesting that this fusion is associated with CRLF2 OE. In survival analysis, no significant differences in 5‐year event‐free survival (EFS) and overall survival were observed between patients with and without CRLF2 OE (70.7 vs. 75.4%, log rank P = 0.68 and 96.4 vs. 82.1%, log rank P = 0.11, respectively). However, a significant difference in 5‐year EFS between CRLF2 OE patients with and without IKZF1 deletion was observed (44.4 vs. 83.1%, log rank P = 0.02). In multivariate analysis, only IKZF1 deletion was a significant predictor of inferior OS (hazard ratio: 2.427, P = 0.04).These findings suggest that CRLF2 OE is not an independent prognostic factor in pediatric BCPALL. © 2014 Wiley Periodicals, Inc.